Mesenchymal Stem Cells (MSCs) as a Potential Therapeutic Strategy in COVID-19 Patients: Literature Research - Coelho, André; Alvites, Rui Damásio; Branquinho, Mariana Vieira; Guerreiro, Susana G.; Maurício, Ana Colette (Frontiers in Cell and Developmental Biology, 2020)
In 2019, an outbreak of an unknown coronavirus – SARS-CoV-2 – responsible for COVID-19 disease, was first reported in China, and evolved into a pandemic of huge dimensions and raised serious concerns for global health. The number of critical cases continues to increase dramatically, while vaccines and specific treatments are not yet available. There are several strategies currently being studied for the treatment of adverse symptoms of COVID-19, that encompass Acute Lung Injury (ALI)/Acute Respiratory Distress Syndrome (ARDS), extensive pulmonary inflammation, cytokine storm, and pulmonary edema, due to virus-induced pneumonia. Mesenchymal stem cells (MSCs) are at the origin of new revolutionary treatments, which may come to be applied in such as Regenerative Medicine, Immunotherapy, Tissue Engineering, and Cell and Molecular Biology due to immunomodulation and anti-inflammatory activity. MSCs have already been studied with positive outcomes for other lung pathologies, thus representing and being identified as an important opportunity for the treatment of COVID-19. It has recently been shown that these cells allow hopeful and effective therapies for serious or critical COVID-19, minimizing its adverse symptoms. In this study we will analyze the MSCs, their origin, differentiation, and therapeutic potential, making a bridge with the COVID-19 disease and its characteristics, as a potential therapeutic strategy but also reporting recent studies where these cell-based therapies were used for the treatment of COVID-19 patients.